Monsoonal forcing of European Ice-Sheet dynamics during the Late Quaternary - Kaboth-Bahr, Stefanie; Bahr, André; Friedrich, Oliver; Pross, Jörg (Geophysical research letters, 2018)
The dynamics of Northern Hemisphere ice sheets during Late Quaternary glacials have yet been dominantly examined from a Lauren tide Ice Sheet perspective, which helped shaping the idea of moisture-starved glacials and small-scale ice volume variability. However, the waxing and waning of the European Ice Sheet (EIS) casts doubt on this perception. Understanding EIS dynamics under glacial boundary conditions iscrucial because its meltwater pulses influence global climate by weakening deep-water formation in the North Atlantic Ocean. Here we show that the advection of subtropical water towards the continental margin of western Europe lead to enhanced moisture availability on the continent and fueled the growth of EIS lobes during glacials. This warm-water pooling was caused by monsoonally paced enhanced Mediterranean Outflow Water (MOW) entrainment that dragged subtropical surface waters towards the European margin. This mechanism presents a yet unrecognized marine-terrestrial pathway that allows low-latitude forcing to shape high-latitude glaciations.
Published online 25 JUL 2018
Gesehen am 17.07.2018
DOI funktioniert nicht 17.07.2018